Real‐time feedback control of voice in cochlear implant recipients - Gautam, Anirudh; Brant, Jason A.; Ruckenstein, Michael J.; Eliades, Steven J. (Laryngoscope investigative otolaryngology, 2020)
Objectives To evaluate feedback‐dependent vocal control in cochlear implant patients using pitch‐shifted auditory feedback. Methods Twenty‐three CI recipients with at least 6 months of implant experience were enrolled. Vocal recordings were performed while subjects repeated the vowel /e/ and vocal signals were altered in real‐time using a digital effects processor to introduce a pitch‐shift, presented back to subjects using headphones. Recordings were analyzed to determine pitch changes following the pitch‐shifted feedback, and results compared to the magnitude of the shift as well as patient demographics. Results Consistent with previous results, CI patients' voices had higher pitches with their implant turned off, a change explainable by increases in vocal loudness without the CI. CI patients rapidly compensated for pitch‐shifted feedback by changing their vocal pitch, but only for larger shifts. Considerable inter‐subject variability was present, and weakly correlated with the duration of implant experience and implant sound thresholds. Conclusions CI patients, like normal hearing individuals, are capable of real‐time feedback‐dependent control of their vocal pitch. However, CI patients are less sensitive to small feedback changes, possibly a result of courser CI frequency precision, and may explain poorer than normal vocal control in these patients. Level of Evidence Level 3b. The effects of cochlear implants on the vocal and speech production have not been well studied. Using pitch‐shifted auditory feedback during vocal production, we show that cochlear implant subjects are capable of real‐time feedback‐dependent vocal control, but exhibit higher variability and thresholds than expected for normal hearing individuals.